2022
DOI: 10.1146/annurev-micro-041320-093442
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a Heterocyst in Cyanobacteria

Abstract: Heterocyst differentiation that occurs in some filamentous cyanobacteria, such as Anabaena sp. PCC 7120, provides a unique model for prokaryotic developmental biology. Heterocyst cells are formed in response to combined-nitrogen deprivation and possess a microoxic environment suitable for nitrogen fixation following extensive morphological and physiological reorganization. A filament of Anabaena is a true multicellular organism, as nitrogen and carbon sources are exchanged among different cells and cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 126 publications
0
38
0
Order By: Relevance
“…Anabaena PCC 7120 ( Anabaena , also known as Nostoc PCC 7120) is a filamentous cyanobacterium and contains 16 genes encoding proteins with a c-di-GMP synthesis or hydrolysis domain, or both ( 28 , 29 ). In this organism, cells, called heterocysts, dedicated to nitrogen fixation, can be induced within 24 h upon combined-nitrogen deprivation ( 30 ). Heterocysts are intercalated among vegetative cells in a semiregular pattern, which constitutes a simple process of developmental pattern formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anabaena PCC 7120 ( Anabaena , also known as Nostoc PCC 7120) is a filamentous cyanobacterium and contains 16 genes encoding proteins with a c-di-GMP synthesis or hydrolysis domain, or both ( 28 , 29 ). In this organism, cells, called heterocysts, dedicated to nitrogen fixation, can be induced within 24 h upon combined-nitrogen deprivation ( 30 ). Heterocysts are intercalated among vegetative cells in a semiregular pattern, which constitutes a simple process of developmental pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocysts are intercalated among vegetative cells in a semiregular pattern, which constitutes a simple process of developmental pattern formation. A number of genes have been identified for the establishment (24 h after the induction) or the maintenance of a heterocyst pattern (48 h or longer after the induction) ( 30 ). It was reported that the inactivation of cdgS ( all2874 ) encoding a c-di-GMP synthetase with a GGDEF domain caused a significant reduction in heterocyst frequency and in cell size of vegetative cells during diazotrophic growth compared to the wild type, and the severity of these phenotypes varied with changes in light intensity ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for the filament to subsist, both end products must be shared and diffused through the filament to the cells that are not capable of synthesizing them. While previous reviews have already Frontiers in Cell and Developmental Biology frontiersin.org compiled the current theories about heterocyst pattern formation (Flores and Herrero, 2010;Herrero et al, 2016;Harish and Seth, 2020;Zeng and Zhang, 2022), in this review, we systematically discuss the different mathematical and computational frameworks that have been used to model the physics of cell differentiation and pattern formation in this system.…”
Section: Introductionmentioning
confidence: 99%
“…The peptidoglycan (PG) represents a contiguous giant macro molecule, which surrounds every single cell, but is fused inside the septum between the cells 3,4 . Molecules determined to traffic intercellularly along the filament have to cross the cytoplasmic membrane of each cell and the septal PG 1,5,6 .To enable this molecular exchange, Nostoc punctiforme and Nostoc exhibit semi-regular 20 nm wide perforations in their septal PG disk, which is referred to as the nanopore array 3,7 . Cell wall amidases are responsible for drilling these 50-150 nanopores per septal PG disk, which are essential for intercellular communication 8-10 (reviewed in: 11 ).…”
mentioning
confidence: 99%
“…The peptidoglycan (PG) represents a contiguous giant macro molecule, which surrounds every single cell, but is fused inside the septum between the cells 3,4 . Molecules determined to traffic intercellularly along the filament have to cross the cytoplasmic membrane of each cell and the septal PG 1,5,6 .…”
mentioning
confidence: 99%